Melatonin entrains the circadian rhythm in the rat pineal N-acetyltransferase activity - Humlová, M; Illnerová, H (Neuroendocrinology, 1990)
It has been recently suggested that in mammals the pineal hormone melatonin may be involved not only in transduction of a photoperiodic information, but in a subtle modulation of a phase of the circadian system as well. This suggestion has been based mainly on data about entrainment of the locomotor activity rhythm by melatonin. The present study was undertaken to check whether melatonin may phase-shift also other circadian rhythms, namely the rhythm in pineal N-acetyltransferase activity which is supposed to drive the rhythmic melatonin production in the rat. 50-day-old male Wistar rats were maintained on a regimen of 10 h of light and 14 h of darkness per day. Vehicle or melatonin (1mg/kg rat weight) was injected subcutaneously just before the dark onset. After a single melatonin injection or after administration of melatonin for 5 successive days or after a 4-day treatment with melatonin and a 1-day withdrawal, the evening N-acetyltransferase rise was phase-advanced relative to the rise in rats treated with vehicle only; the phase shift was larger after a repeated than after a single melatonin injection. Under all above-mentioned paradigms of melatonin administration, the morning N-acetyltransferase decline was less phase-advanced than the evening rise. Persistence of the phase advance of the N-acetyltransferase rise after withdrawal of melatonin treatment and a larger phase shift after a repeated than after a single melatonin administration suggest that melatonin may entrain directly a circadian pacemaker controlling the N-acetyltransferase rhythm and affect thus its own rhythmic production.
Keywords: inbrední kmeny potkanů; Arylamine N-Acetyltransferase; Rats, Inbred Strains; Rats; epifýza mozková; krysa rodu Rattus; cirkadiánní rytmus; Animals; Circadian Rhythm; Male; Melatonin; Pineal Gland; injekce subkutánní; arylamin-N-acetyltransferasa; mužské pohlaví; melatonin; Injections, Subcutaneous; zvířata